2000
DOI: 10.1021/om000617p
|View full text |Cite
|
Sign up to set email alerts
|

Mono-, Di-, and Tricarboxylic Acids:  Central Building Blocks for the Formation of Multinuclear Transition Metal Complexes

Abstract: The synthesis and characterization of the di-, tetra-, and hexanuclear titanium(IV)-copper-(I) carboxylates {[Ti](CtCSiMe 3 ) 2 }CuO 2 CR 2 (3) {3a: R 2 ) Me, 3b: R 2 ) C 6 H 5 , 3c: R 2 ) CH 2 C 6 H 5 , 3d: R 2 ) CHdCMe 18) is described. All of these complexes are easily accessible by the reaction of {[Ti](CtCR 1 ) 2 }CuMe (1a: R 1 ) SiMe 3 , 1b: R 1 ) t Bu) with the corresponding carboxylic acids in different stoichiometric ratios of the reactants. Furthermore, the preparation and reaction chemistry of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The synthesis of organometallic π-tweezer-based copper (I) acetylides is possible by the reaction of [{[Ti](μ-σ,π-CCSiMe 3 ) 2 }CuCH 3 ] ([Ti] = (η 5 -C 5 H 4 SiMe 3 ) 2 Ti) with CH-acidic alkynes . Nevertheless, attempts to obtain 1-(FcCC)-3-[( t Bu 2 bpy)(CO) 3 ReCC]-5-[{[Ti](μ-σ,π-CCSiMe 3 ) 2 }CuCC]C 6 H 3 by reacting 8 with [{[Ti](μ-σ,π-CCSiMe 3 ) 2 }CuCH 3 ] in tetrahydrofuran at room temperature failed, presumably due to the steric bulkiness of the bis(alkynyl)titanocene and the [( t Bu 2 bpy)(CO) 3 Re] fragments.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of organometallic π-tweezer-based copper (I) acetylides is possible by the reaction of [{[Ti](μ-σ,π-CCSiMe 3 ) 2 }CuCH 3 ] ([Ti] = (η 5 -C 5 H 4 SiMe 3 ) 2 Ti) with CH-acidic alkynes . Nevertheless, attempts to obtain 1-(FcCC)-3-[( t Bu 2 bpy)(CO) 3 ReCC]-5-[{[Ti](μ-σ,π-CCSiMe 3 ) 2 }CuCC]C 6 H 3 by reacting 8 with [{[Ti](μ-σ,π-CCSiMe 3 ) 2 }CuCH 3 ] in tetrahydrofuran at room temperature failed, presumably due to the steric bulkiness of the bis(alkynyl)titanocene and the [( t Bu 2 bpy)(CO) 3 Re] fragments.…”
Section: Resultsmentioning
confidence: 99%
“…For a comprehensive patent covering CVD applications of copper(I) oxalates, see: Kö hler & Meyer (2004). For related copper(I) oxalate complexes, see: Frosch et al (2000); He et al (2008); Teichgrä ber et al (2005). For the chemical fixation of CO 2 to form oxalates, see: Savé ant (2008).…”
Section: Related Literaturementioning
confidence: 99%
“…Another early example of a copper(I) oxalate complex was a dinuclear triphenylphosphine complex reported by Gimeno et al [7], structurally characterized later by the Lang group [8], which also reported a few other copper(I) oxalate phosphine complexes in the same paper. Lang et al also reported a copper(I) oxalate complex with a bis(trimethylsilylpentadienyl)titanium bis(trimethylsilylacetylide) tweezer ligand, but the complex was not structurally characterized [9]. In a couple of seminal studies by Meyer, Köhler, and coworkers [1,2], a series of copper(I) oxalate complexes with alkyne, alkene and isocyanide ligands were synthesized, a number of which were structurally characterized, not including alkene complexes.…”
Section: Introductionmentioning
confidence: 99%